The question of the Epipalaeolithic and Mesolithic in Croatia - Paunović, Maja; Karavanić, Ivor (1999)
The paper presents three, out of about ten registered, Epipaleolithic and Mesolithic sites in Croatia, the only ones that were systematically excavated (Velika Pećina, Vindija, Kopačina). Among the stone material, endscrapers are frequent. The geometrically shaped microlithes are very rare. The reason for that would more probably be the rare use of the sifting method on sediment. The scare archaeological material on continental sites could also be caused by discontinued sedimentation or by erosion of part of the Epipaleolithic and Mesolithic cultural levels.
Projekt MZOS
Projekt MZOS
ENG